A Crosssectional Study on Knowledge, Attitude and Practice on Pressure Ulcer among Nurses in Jigme Dorji Wangchuk National Referral Hospital (JDWNRH) (International Journal of Nursing Care, 2020)
The increased incidence of pressure ulcers among inpatient patients has been reported in JDWNRH. Asa result, there was an increase in the length of hospitalization, over utilization of resources and affectspatient’s satisfaction. There was also a lack of adequate evidence on knowledge, attitude and practice foreffective prevention of pressure ulcers. The study was conducted to study the knowledge, attitude, andpractice of pressure ulcers among nurses of JDWNRH. Cross-sectional was used among 389 nurses workingin all inpatients department. The results found that the knowledge on pressure sore was good (64%) but theattitude (75.1%) and Practice (93.1%) to prevent pressure ulcer was low. Scientific analysis also showed thatknowledge had a significant correlation with working experience (p=0.034), which reveals that the longerthe duration in the service, the more the knowledge was gained. Subsequently, the more the knowledge wasgained, the practice on prevention on pressure ulcer increases (p=0.036). The study found out that retentionof the experienced nurses is extremely important because CME updates the knowledge, which eventuallyimproves the patient’s care whereas behaviour change remains challenging because of individual attitudeand perception.
Keywords: Incidence, pressure ulcer, hospitalization, knowledge, attitude, practice, working experience, prevention.